"Busybodies With Time on Their Hands": Accountability, Research, and Resistance. (March 2023) - Bates, Stephen
In a common pattern, journalists reject outside criticism and denounce the critics. Resistance to criticism sometimes follows a second pattern, one largely overlooked by scholars: Journalists kill a large-scale research project before it gets under way and thereby prevent criticisms from even being articulated. This monograph examines four major research projects that got canceled in the face of opposition from the press: studies of international news in the early 1920s, public opinion about the press in the late 1930s, press accuracy and ownership in the late 1930s, and coverage of a presidential campaign in the mid-1950s.